Social Media Marketing Against Decisions Purchase at Kopi Kenangan Batam - Tirta Mulyadi; Victor Prasetya, Hartoyo; Arief Yanto Rukmana; Rusydi Fauzan (STIE Amkop Makassar, 2023)
The purpose of this research is to see the influence of Social Media marketing on the dependent variable, namely consumer purchasing decisions at Kopi Kenangan in Batam. The explanatory research technique is the technique used in this research, and uses hypothesis testing to clarify the cause and effect relationship between research variables. By taking a quantitative approach, collecting data and information using a questionnaire which will be distributed to customers of Kedai Kopi Kenangan Batam. This research used the population of Kopi Kenangan consumers in Batam with an age range of 21-26 years as research objects, which used 88 respondents as samples using a purposive sampling technique. After conducting research on 88 respondents, the results showed that the variables Social Media, feel, think, act and relate as dependent variables simultaneously influenced consumer purchasing decisions as the dependent variable